Trois auteurs aux limites de l’île J.-L. Coudray, J. Banville, S. Dagerman - Éric Fougère (Carnets, 2019)
To evoke the selection of a place such as an island in the novel implies establishing three distinct levels: referential (generally, the reference is to Robinson), textual (re-writing is involved where the island appears as through a palimpsest), and conceptual (there is something of an idea in the nature of islands as there is something of an island in the nature of ideas). This, in turn, entails three separate approaches: geographic (insular space stricto sensu), geo-poetical (fictionalization of the insular space), and geo-symbolical (allegories linked to the essence of an island). Jean-Luc Coudray’s Les deux îles de Robinson, John Banville’s Ghosts and Stig Dagerman’s Island of the Doomed have it in common that they de-realise the island, enhancing its metaphorical and metaphysical dimensions. If the island is the locus for the novels it relates to, it is because the image it carries is interiorised by characters who are human islands within a hostile world where reality and fiction are indissociable and where the island, as if mirrored, en abyme, or concanated, reaches the outer limits of its representation.